Featured Cover - Lin, Chia‐Pin (J Clin Hypertens (Greenwich), 2020)
The cover image is based on the Original Paper Fixed‐dose combination of amlodipine and atorvastatin improves clinical outcomes in patients with concomitant hypertension and dyslipidemia by Chia‐Pin Lin, Ying‐Chang Tung et al., https://doi.org/10.1111/jch.14016. [Image: see text]